The Emerging Adulthood Years: Finding One's Way in Career and Intimate Love Relationships. Issue 1 (31st March 2017) - Shulman, Shmuel
ABSTRACT: This study examines career and intimate love pathways in 100 Israeli emerging adults (fifty-four men) who were followed from age twenty-two to twenty-nine. In a semistructured interview at the age of twenty-nine, participants were asked about current work and educational status and changes in recent years. They were also asked to reflect on the meaning of the processes they followed. Following the completion of the career interview, participants were asked to talk about their current romantic status, their past romantic experiences, difficulties in relationships and past separations, and how they coped with these. Analyses of interviews yielded four distinctive career pursuit pathways and four intimate love pathways that varied on the continuum of stability–variability, and were associated with different levels of concurrent well-being. Analysis of the interviews showed that changes that young people make along the way do not necessarily indicate confusion, but might represent their efforts to find their own paths toward settling down. Personality measures, such as self-criticism, dependency and efficacy, measured seven years earlier, predicted pathway affiliation at age twenty-nine. In addition, parental support was found to serve as a protective or risk factor associated with adaptive pursuit of career and intimate love goals. By employing this mixed-method approach, the findings demonstrate the diverse development of career and intimate love pathways during emerging adulthood, and indicate the importance of personality and parental support in the process of development during the transition to adulthood.